Validation of manual to complement the transition of care at discharge from intensive care - Martina Zucchetti; Isis Marques Severo; Isabel Cristina Echer; Daniela dos Santos Marona Borba; Carmen Lucia Silva Nectoux; Karina de Oliveira Azzolin (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective To develop and validate an interprofessional manual for the transfer of care to critically ill adult patients. Method Methodological study, conducted from January to September 2019. The content of the manual was listed by the multidisciplinary team of an adult Intensive Care Unit, in southern Brazil. In the validation by the professionals, the content validity index (CVI) of the evaluation questions was calculated. Subsequently, a sample of 30 patients/caregivers evaluated the product, and the arithmetic mean of the questions was calculated. Results The manual addresses important information and care transition guidance for patients and caregivers, from admission to the intensive care to discharge to the inpatient unit. The professionals' CVI ranged from 0.9 to 1. The arithmetic mean of 17 patients and 13 caregivers was 3.8. Final considerations The validated manual can be used as a complementary material for health education and qualify the transition of care.